High-strength and high-performance radiation-proof concrete and preparation process thereof

By using copper-plated microwire steel fibers and specific mineral blends in concrete, the problem of insufficient radiation barrier effect and strength in engineering applications is solved, and high-strength and high-performance radiation-proof concrete is achieved.

CN119874277APending Publication Date: 2025-04-25EAST CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411852598.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-25

Smart Images

  • Figure CN119874277A_ABST
    Figure CN119874277A_ABST
Patent Text Reader

Abstract

The high-strength and high-performance radiation-proof concrete is prepared from water, a cementing material, fine aggregate, special-shaped steel shots, a water reducing agent and fibers, the cementing material is composed of cement and a mineral admixture, the mineral admixture is composed of fly ash and barite powder according to the weight ratio of 1: (1-2), and the fibers are copper-plated microfilament steel fibers coated with epoxy resin on the surfaces; the concrete is prepared from the following components in parts by weight: 140 to 180 parts of water, 200 to 400 parts of cement, 100 to 200 parts of mineral admixture, 1200 to 1500 parts of fine aggregate which is lead-zinc ore sand with the particle size of 0.1 to 0.6 mm, and 600 to 1000 parts of lead-zinc ore sand with the particle size of 0.6 to 1.18 mm; 100-500 parts of special-shaped steel shots with the particle size of 0.1-2 mm, 10-20 parts of a polycarboxylic acid high-efficiency water reducing agent and 30-50 parts of fibers. The concrete provided by the invention has enough strength, improves the radiation blocking effect, and improves the overall comprehensive performance of the concrete. The highest strength of the concrete can reach 140 MPa. While enough concrete strength is guaranteed, the thickness of the concrete during design is effectively reduced, and materials are saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to high-strength and high-performance radiation-proof concrete and a preparation process thereof. Background Art

[0002] Since the rapid development of science and technology, nuclear technology has been closely related to our lives and has been widely used in many fields such as nuclear power, military, education, scientific research, and medical treatment. At present, the commonly used radiation protection materials in my country include lead plates, steel plates, polymers, concrete, etc. These materials have a certain radiation blocking effect on radiation, among which concrete has the advantages of easy construction, low cost, good mechanical properties and durability. However, in actual engineering applications, the existing concrete still has some performance deficiencies, such as poor radiation blocking effect and insufficient strength. Summary of the invention

[0003] The purpose of the present invention is to provide a high-strength and high-performance radiation-proof concrete and its preparation process in view of the deficiencies of the prior art. The concrete has sufficient strength and improves the radiation blocking effect and the overall comprehensive performance of the concrete. The strength of this type of concrete can reach up to 140MPa. While ensuring sufficient concrete strength, the thickness of the concrete in the design is effectively reduced, saving materials. According to actual conditions, it can provide an option for underground radiation protection projects.

[0004] A high-strength and high-performance radiation-proof concrete, comprising water, cementitious material, fine aggregate, special-shaped steel shot, water reducing agent and fiber; the cementitious material comprises cement and mineral admixture, the mineral admixture comprises fly ash and barite powder in a weight ratio of 1:1-2, and the fiber is copper-plated microfilament steel fiber with epoxy resin coated on the surface; the concrete comprises, by weight: 140-180 parts of water, 200-400 parts of cement, 100-200 parts of mineral admixture, 1200-1500 parts of fine aggregate, 600-1000 parts of lead-zinc ore sand with a particle size of 0.1-0.6mm, 100-500 parts of special-shaped steel shot with a particle size of 0.1-2mm, 10-20 parts of polycarboxylic acid high-efficiency water reducing agent, and 30-50 parts of fiber.

[0005] Preferably, the concrete includes the following raw material components in parts by weight: 250 parts of cement, 150 parts of mineral admixture, 1383 parts of lead-zinc ore with a particle size of 0.1-0.6 mm, 847 parts of lead-zinc ore with a particle size of 0.6-1.18 mm, 18 parts of polycarboxylic acid high-efficiency water reducer, 39 parts of fiber, 160 parts of water; 147 parts of special-shaped steel shot with a particle size of 0.1-2 mm, and the mineral admixture is composed of fly ash and barite powder in a weight ratio of 1:1.

[0006] Preferably, the lead-zinc ore contains 2%-5% lead, 8%-15% zinc, 20%-30% sulfur and 50%-65% oxides, wherein the oxides include one or more of silicon, sulfur, iron and cadmium oxides, and the specific gravity of the lead-zinc ore is 4.5 g / cm 3 .

[0007] Preferably, the particle size of the special-shaped steel shot is 0.1-2 mm, and the specific gravity of the special-shaped steel shot is 7.8 g / cm 3 The surface of the special-shaped steel shot has a circle of concave holes to increase the bite force with concrete.

[0008] Preferably, the fly ash has a particle size of 0.5-100 μm, a water content of 1-5%, a sulfur trioxide content of 0.5-1%, and a loss on ignition of 1.5-3%;

[0009] The barite powder has a particle size of 0.1-1 μm and a bulk density of 3200 kg / m 3 , moisture content is less than 5%.

[0010] Preferably, the copper-plated microfilament steel fiber includes a layer of copper plated on the surface of the steel fiber. The copper-plated layer can protect the steel fiber from oxidation and corrosion and extend its service life. The epoxy resin has the characteristics of strong bonding, impact resistance, toughness, and good resistance to deformation.

[0011] Preferably, the water reduction rate of the polycarboxylic acid high-efficiency water-reducing agent is 18%, and the 1h slump retention rate is not less than 95%.

[0012] As preferably, the barite powder is pretreated: the barite powder is calcined by step-by-step calcination including at least four calcination stages, the calcination temperature of the first stage is 105-110°C, the calcination temperature of the second stage is 450-500°C, the calcination temperature of the third stage is 850-900°C, and the calcination temperature of the fourth stage is not less than 1000°C (generally 1000°C-1300°C), wherein the insulation time of the first three stages shall not be less than 30min (generally 30-120min), the insulation time of the fourth stage shall not be less than 1h (generally 1h-3h), and the heating rate of each stage shall not be higher than 10°C / min (generally 2-10°C / min). Compared with ordinary calcination, the thermal stability and hardness of the barite powder after step-by-step calcination can be improved by 5%-11%.

[0013] A method for preparing high-performance radiation-proof concrete specifically comprises the following steps:

[0014] According to weight percentage: 200-400 parts of cement, 100-200 parts of mineral admixtures, 15-25 parts of fibers, 1200-1500 parts of lead-zinc ore with a particle size of 0.1-0.6mm, 600-1000 parts of lead-zinc ore with a particle size of 0.6-1.18mm, and 100-500 parts of special-shaped steel shots are added to the mixer, mixed for the first time, and 15-25 parts of fibers are added for the second mixing to obtain a mixture; to ensure that the fibers are evenly distributed in the concrete. This helps to give full play to the reinforcing effect of the fibers; then 140-180 parts of water and 10-20 parts of polycarboxylic acid high-efficiency water reducing agent are added to the mixture to make it fully mixed, and stirred for the third time until it is uniform to obtain high-performance radiation-proof concrete.

[0015] Preferably, the first stirring time is 2-3 min, the second stirring time is 0.5-1 min, the third stirring time is 5-10 min, and the stirring speed is 60 rpm. Preferably, the elastic modulus of the copper-plated microfilament steel fiber is 200 GPa.

[0016] The properties of the copper-plated microfilament steel fiber are shown in Table 1.

[0017] Table 1

[0018] Length(mm) Aspect Ratio Density (kg / m3) Melting point(℃) Tensile strength(MPa) Elastic modulus(GPa) 13 60 7850 1500 3100 200

[0019] The properties of the epoxy resin are shown in Table 2.

[0020] Table 2

[0021]

[0022] Beneficial effects of the present invention:

[0023] 1. The copper-plated microfilament steel fiber of the present invention is coated with epoxy resin. The epoxy resin model is JT-1030, which has the characteristics of strong bonding force, impact resistance, toughness, and good resistance to deformation. Compared with directly using copper-plated microfilament steel fiber, it can effectively improve the compressive strength of concrete by 5%-10%;

[0024] 2. The cementitious material of the present invention is composed of cement and mineral admixtures. The mineral admixtures are fly ash and barite powder in a ratio of 1:1-2. The prepared cementitious material can effectively increase the apparent density of concrete, reduce water consumption, and increase the content of crystal water inside the concrete;

[0025] 3. The concrete of the present invention has unique components and proportions, including 140-180 parts of water, 200-400 parts of cement, 100-200 parts of mineral admixtures, 1200-1500 parts of lead-zinc ore with a particle size of 0.1-0.6 mm, 600-1000 parts of lead-zinc ore with a particle size of 0.6-1.18 mm, 10-20 parts of polycarboxylic acid high-efficiency water reducing agent, and 30-50 parts of fiber. While ensuring the working performance of the concrete, the mechanical properties and apparent density of the concrete are improved, and the overall radiation resistance of the concrete is improved.

[0026] 4. The present invention forms a cementing substance inside the concrete by using fly ash and cement, thereby reducing the porosity of the concrete and greatly improving the compactness of the concrete. The cementing substance and the lead-zinc ore sand are bonded to each other, and the interaction between the components ensures the strength of the concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a fiber structure diagram of the present invention.

[0028] Figure 2 It is a structural diagram of the special-shaped steel shot of the present invention.

[0029] Figure numerals: steel fiber 1, epoxy resin 2, special-shaped steel shot 3. DETAILED DESCRIPTION

[0030] The present invention is further described below by way of examples.

[0031] In order to better understand the technical content of the present invention, specific embodiments are given as follows.

[0032] The embodiments of the present disclosure are not necessarily intended to include all aspects of the invention.It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways.

[0033] The present invention provides a high-performance radiation-proof concrete which improves the radiation-proof performance of the concrete while ensuring the working performance and mechanical properties of the concrete through the synergy of various components.

[0034] A high-strength and high-performance radiation-proof concrete, comprising water, cementitious material, fine aggregate, special-shaped steel shot, water reducing agent and fiber; the cementitious material comprises cement and mineral admixture, the mineral admixture comprises fly ash and barite powder in a weight ratio of 1:1-2, and the fiber is copper-plated microfilament steel fiber with epoxy resin coated on the surface; the concrete comprises, by weight: 140-180 parts of water, 200-400 parts of cement, 100-200 parts of mineral admixture, 1200-1500 parts of fine aggregate, 600-1000 parts of lead-zinc ore sand with a particle size of 0.1-0.6mm, 100-500 parts of special-shaped steel shot with a particle size of 0.1-2mm, 10-20 parts of polycarboxylic acid high-efficiency water reducing agent, and 30-50 parts of fiber.

[0035] Preferably, the concrete includes the following raw material components in parts by weight: 250 parts of cement, 150 parts of mineral admixture, 1383 parts of lead-zinc ore with a particle size of 0.1-0.6 mm, 847 parts of lead-zinc ore with a particle size of 0.6-1.18 mm, 18 parts of polycarboxylic acid high-efficiency water reducer, 39 parts of fiber, 160 parts of water; 147 parts of special-shaped steel shot with a particle size of 0.1-2 mm, and the mineral admixture is composed of fly ash and barite powder in a weight ratio of 1:1.

[0036] Preferably, the lead-zinc ore contains 2%-5% lead, 8%-15% zinc, 20%-30% sulfur and 50%-65% oxides, wherein the oxides include one or more of silicon, sulfur, iron and cadmium oxides, and the specific gravity of the lead-zinc ore is 4.5 g / cm 3 .

[0037] Preferably, the particle size of the special-shaped steel shot is 0.1-2 mm, and the specific gravity of the special-shaped steel shot is 7.8 g / cm 3 The surface of the special-shaped steel shot has a circle of concave holes to increase the bite force with concrete.

[0038] Preferably, the fly ash has a particle size of 0.5-100 μm, a water content of 1-5%, a sulfur trioxide content of 0.5-1%, and a loss on ignition of 1.5-3%;

[0039] The barite powder has a particle size of 0.1-1 μm and a bulk density of 3200 kg / m 3 , moisture content is less than 5%.

[0040] Preferably, the copper-plated microfilament steel fiber includes a layer of copper plated on the surface of the steel fiber. The copper-plated layer can protect the steel fiber from oxidation and corrosion and extend its service life. The epoxy resin has the characteristics of strong bonding, impact resistance, toughness, and good resistance to deformation.

[0041] Preferably, the water reduction rate of the polycarboxylic acid high-efficiency water-reducing agent is 18%, and the 1h slump retention rate is not less than 95%.

[0042] As preferably, the barite powder is pretreated: the barite powder is calcined by step-by-step calcination including at least four calcination stages, the calcination temperature of the first stage is 105-110°C, the calcination temperature of the second stage is 450-500°C, the calcination temperature of the third stage is 850-900°C, and the calcination temperature of the fourth stage is not less than 1000°C (generally 1000°C-1300°C), wherein the insulation time of the first three stages shall not be less than 30min (generally 30-120min), the insulation time of the fourth stage shall not be less than 1h (generally 1h-3h), and the heating rate of each stage shall not be higher than 10°C / min (generally 2-10°C / min). Compared with ordinary calcination, the thermal stability and hardness of the barite powder after step-by-step calcination can be improved by 5%-11%.

[0043] A method for preparing high-strength and high-performance radiation-proof concrete, specifically comprising the following steps:

[0044] According to the weight percentage, 200-400 parts of cement, 100-200 parts of mineral admixtures, 15-25 parts of copper-plated microfilament steel fibers, 1200-1500 parts of lead-zinc ore with a particle size of 0.1-0.6 mm, 600-1000 parts of lead-zinc ore with a particle size of 0.6-1.18 mm, and 100-500 parts of special-shaped steel shots are added to the mixer, stirred and mixed for the first time, and 15-25 parts of copper-plated microfilament steel fibers are added for the second stirring to obtain a mixture; to ensure the uniform distribution of steel fibers in concrete. This helps to give full play to the reinforcing effect of steel fibers; then 140-180 parts of water and 10-20 parts of polycarboxylic acid high-efficiency water reducing agent are added to the mixture to make it enter a fully mixed state, and stirred for the third time until it is uniform to obtain high-performance radiation-proof concrete.

[0045] Preferably, the first stirring time is 2-3 min, the second stirring time is 0.5-1 min, the third stirring time is 5-10 min, and the stirring speed is 60 rpm.

[0046] Preferably, the elastic modulus of the copper-plated microfilament steel fiber is 200 GPa.

[0047] The properties of the copper-plated microfilament steel fiber are shown in Table 1.

[0048] Table 1

[0049] Length(mm) Aspect Ratio Density (kg / m3) Melting point(℃) Tensile strength(MPa) Elastic modulus(GPa) 13 60 7850 1500 3100 200

[0050] The properties of the epoxy resin are shown in Table 2.

[0051] Table 2

[0052]

[0053] In a preferred embodiment, the elastic modulus of the copper-plated microfilament steel fiber is 200 GPa.

[0054] In a preferred embodiment, the cement is silicate cement, and the strength grade of the cement is 52.5.

[0055] For better understanding, the present invention is further described below in conjunction with several specific examples, but the preparation process is not limited thereto, and the content of the present invention is not limited thereto.

[0056] The material specifications used in the following examples and comparative examples are as follows:

[0057] Cement: Portland cement with strength grade 52.5;

[0058] Fly ash: particle size is 0.5-100μm, water content is 5%, sulfur trioxide content is 0.5%, and loss on ignition is 3%;

[0059] Barite powder: particle size is 0.1-1μm, bulk density is 3200kg / m 3 , moisture content is less than 5%;

[0060] Polycarboxylic acid high-efficiency water reducing agent: water reduction rate is 18%;

[0061] Copper-plated microfilament steel fiber: elastic modulus is 200GPa;

[0062] Lead-zinc ore: Shanghai Keju Industrial Co., Ltd.

[0063] [Example 1]

[0064] 250 parts of cement, 150 parts of mineral admixture, the mineral admixture is composed of fly ash and barite powder in a weight ratio of 1:1, 1383 parts of lead-zinc ore with a particle size of 0.1-0.6mm, 847 parts of lead-zinc ore with a particle size of 0.6-1.18mm, 147 parts of special-shaped steel shots with a particle size of 0.1-2mm, and 20 parts of copper-plated microfilament steel fiber coated with epoxy resin are added into a mixer and stirred for 2 minutes before mixing evenly; 19 parts of copper-plated microfilament steel fiber coated with epoxy resin are added and stirred for another 1 minute, followed by adding 18 parts of polycarboxylic acid high-efficiency water reducing agent and 160 parts of water to make it enter a fully mixed state, stirring for 8 minutes, and stirring until it is evenly mixed to obtain high-performance radiation-proof concrete.

[0065] [Example 2]

[0066] 250 parts of cement, 150 parts of mineral admixture, the mineral admixture is composed of fly ash and barite powder in a weight ratio of 1:1, 1294 parts of lead-zinc ore with a particle size of 0.1-0.6mm, 924 parts of lead-zinc ore with a particle size of 0.6-1.18mm, 147 parts of special-shaped steel shots with a particle size of 0.1-2mm, and 20 parts of copper-plated microfilament steel fiber coated with epoxy resin are added into a mixer, stirred for 2 minutes and then mixed evenly; 19 parts of copper-plated microfilament steel fiber coated with epoxy resin are added and stirred for another 1 minute; then 18 parts of polycarboxylic acid high-efficiency water reducing agent and 160 parts of water are added to make them enter a fully mixed state, stirred for 8 minutes, and stirred until uniform to obtain high-performance radiation-proof concrete.

[0067] [Example 3]

[0068] 250 parts of cement, 150 parts of mineral admixture, the mineral admixture is composed of fly ash and barite powder in a weight ratio of 1:1, 1216 parts of lead-zinc ore with a particle size of 0.1-0.6mm, 983 parts of lead-zinc ore with a particle size of 0.6-1.18mm, 147 parts of special-shaped steel shots with a particle size of 0.1-2mm, and 20 parts of copper-plated microfilament steel fiber coated with epoxy resin are added into a mixer and stirred for 2 minutes before mixing evenly; 19 parts of copper-plated microfilament steel fiber coated with epoxy resin are added and stirred for another 1 minute; then 18 parts of polycarboxylic acid high-efficiency water reducer and 160 parts of water are added to make it enter a fully mixed state, stirred for 8 minutes, and stirred until it is evenly mixed to obtain high-performance radiation-proof concrete.

[0069] [Comparative Example 1]

[0070] 250 parts of cement, 150 parts of mineral admixture, the mineral admixture is composed of fly ash and barite powder in a weight ratio of 1:1, 1634 parts of river sand with a particle size of 0.1-0.6mm, 1176 parts of river sand with a particle size of 0.6-1.18mm, 147 parts of special-shaped steel shots with a particle size of 0.1-2mm, and 20 parts of copper-plated microfilament steel fibers coated with epoxy resin are added into a mixer and stirred for 2 minutes before mixing evenly; 19 parts of copper-plated microfilament steel fibers coated with epoxy resin are added and stirred for another 1 minute, followed by adding 18 parts of polycarboxylic acid high-efficiency water reducing agent and 160 parts of water to make them enter a fully mixed state, stirring for 8 minutes, and stirring until uniform to obtain high-performance radiation-proof concrete.

[0071] [Comparative Example 2]

[0072] 250 parts of cement, 150 parts of mineral admixture, the mineral admixture is composed of fly ash and barite powder in a weight ratio of 1:1, 1383 parts of lead-zinc ore with a particle size of 0.1-0.6mm, 847 parts of lead-zinc ore with a particle size of 0.6-1.18mm, 147 parts of special-shaped steel shots with a particle size of 0.1-2mm, and 20 parts of ordinary copper-plated microfilament steel fiber are added into a mixer and stirred for 2 minutes before mixing evenly; 19 parts of ordinary copper-plated microfilament steel fiber are stirred for 1 minute, and then 18 parts of polycarboxylic acid high-efficiency water reducing agent and 160 parts of water are added to make it enter a fully mixed state, and stirred for 8 minutes. High-performance radiation-proof concrete is obtained by stirring until it is uniform.

[0073] [Comparative Example 3]

[0074] 250 parts of cement, 150 parts of mineral admixture, the mineral admixture consists of fly ash and barite powder in a weight ratio of 1:1, 1383 parts of lead-zinc ore with a particle size of 0.1-0.6mm, 847 parts of lead-zinc ore with a particle size of 0.6-1.18mm, 147 parts of ordinary steel shot with a particle size of 0.1-2mm, and 20 parts of copper-plated microfilament steel fiber coated with epoxy resin are added into a mixer and stirred for 2 minutes before mixing evenly; 19 parts of copper-plated microfilament steel fiber coated with epoxy resin are added and stirred for another 1 minute, followed by adding 18 parts of polycarboxylic acid high-efficiency water reducing agent and 160 parts of water to make it enter a fully mixed state, stirring for 8 minutes, and stirring until it is evenly mixed to obtain high-performance radiation-proof concrete.

[0075] [Comparative Example 4]

[0076] 250 parts of cement, 150 parts of mineral admixture, the mineral admixture is composed of fly ash and barite powder in a weight ratio of 1:1, 1383 parts of lead-zinc ore with a particle size of 0.1-0.6mm, 847 parts of lead-zinc ore with a particle size of 0.6-1.18mm, 147 parts of special-shaped steel shots with a particle size of 0.1-2mm, and 39 parts of copper-plated microfilament steel fibers coated with epoxy resin are added into a mixer and stirred for 3 minutes before mixing evenly; then 18 parts of polycarboxylic acid high-efficiency water reducing agent and 160 parts of water are added to make them enter a fully mixed state, stirred for 8 minutes, and stirred until uniform to obtain high-performance radiation-proof concrete.

[0077] [Comparative Example 5]

[0078] 250 parts of cement, 150 parts of mineral admixture, the mineral admixture consists of fly ash, 1383 parts of lead-zinc ore with a particle size of 0.1-0.6mm, 847 parts of lead-zinc ore with a particle size of 0.6-1.18mm, 147 parts of special-shaped steel shots with a particle size of 0.1-2mm, and 20 parts of copper-plated microfilament steel fiber coated with epoxy resin are added into a mixer and stirred for 2 minutes before being evenly mixed; 19 parts of copper-plated microfilament steel fiber coated with epoxy resin are added and stirred for 1 minute, followed by adding 18 parts of polycarboxylic acid high-efficiency water reducing agent and 160 parts of water to make them enter a fully mixed state, stirring for 8 minutes, and stirring until evenly mixed to obtain high-performance radiation-proof concrete.

[0079] The concrete obtained from Examples 1-3 and Comparative Examples 1-5 was subjected to performance tests.

[0080] Testing method: The concrete mixture prepared by the above components according to the above process is molded into specimens according to standard requirements and cured for 28 days under standard environment. The working performance of the concrete mixture is tested according to the "Test Method for Performance of Ordinary Concrete Mixtures", and the mechanical strength of the concrete test block is tested according to the "Standard for Test Method for Mechanical Properties of Ordinary Concrete". The radiation protection performance is numerically simulated by geant4, and the calculation results are expressed as linear attenuation coefficients.

[0081] The results are shown in Tables 3 and 4 below.

[0082] Table 3

[0083]

[0084]

[0085] Table 4

[0086]

[0087] By adding comparative example 1 and comparing it with the embodiment, it can be found that after the heavy aggregate is changed to river sand, the overall working performance becomes better, while the overall strength is reduced, and the overall radiation protection ability of the concrete is reduced; after the fiber is changed to ordinary copper-plated microfilament steel fiber, although the overall apparent density does not decrease, the workability in construction becomes worse, and the strength is also reduced, and the radiation protection performance does not change much; after the special-shaped steel shot is replaced by ordinary steel shot, the overall apparent density does not change much, and because the contact between the ordinary steel shot and the concrete is poor, the workability of the concrete in construction becomes worse, and the mechanical properties of the concrete are greatly affected, the mechanical properties of the concrete are significantly reduced, and the radiation protection performance changes less; and the fiber admixture is added at one time, the overall apparent density does not decrease, but the workability in construction becomes worse. In the experiment, some samples will show fiber agglomeration, so the strength is also reduced, and the radiation protection performance remains unchanged; after the fly ash replaces the barite powder, the overall apparent density decreases significantly, and the strength is also reduced, the workability in construction remains basically unchanged, and the radiation protection performance decreases as a whole.

[0088] Added radiation protection (effect) comparative data and analysis,

[0089] 1. The copper-plated microfilament steel fiber of the present invention is coated with epoxy resin. The epoxy resin model is JT-1030, which has the characteristics of strong bonding force, impact resistance, toughness, and good resistance to deformation. Compared with directly using copper-plated microfilament steel fiber, it can effectively improve the compressive strength of concrete by 5%-10%;

[0090] 2. The cementitious material of the present invention is composed of cement and mineral admixtures. The mineral admixtures are fly ash and barite powder in a 1:1 ratio. The prepared cementitious material can effectively increase the apparent density of concrete, reduce water consumption, and increase the content of crystal water inside the concrete;

[0091] 3. The step-by-step calcination of the barite powder used in the present invention includes at least four calcination stages. The calcination temperature of the first stage is 105-110°C, the calcination temperature of the second stage is 450-500°C, the calcination temperature of the third stage is 850-900°C, and the calcination temperature of the fourth stage is not less than 1000°C (generally 1000°C-1300°C). The insulation time of the first three stages shall not be less than 30min (generally 30-120min), and the insulation time of the fourth stage shall not be less than 1h (generally 1h-3h). The heating rate of each stage shall not be higher than 10°C / min (generally 2-10°C / min). Compared with ordinary calcination, the thermal stability and hardness of the barite powder after step-by-step calcination can be improved by 5%-11%.

[0092] 4. The present invention further improves the apparent density and radiation protection performance of concrete by adding special-shaped steel shots to concrete;

[0093] 5. The concrete of the present invention has unique components and proportions, including 140-180 parts of water, 200-400 parts of cement, 100-200 parts of mineral admixtures, 1200-1500 parts of lead-zinc ore with a particle size of 0.1-0.6 mm, 600-1000 parts of lead-zinc ore with a particle size of 0.6-1.18 mm, 10-20 parts of polycarboxylic acid high-efficiency water reducing agent, and 30-50 parts of fiber. While ensuring the working performance of the concrete, the mechanical properties and apparent density of the concrete are improved, and the overall radiation resistance of the concrete is improved.

[0094] 6. The present invention forms a cementing substance inside the concrete by using fly ash and cement, thereby reducing the porosity of the concrete and greatly improving the compactness of the concrete. The cementing substance and the lead-zinc ore sand are bonded to each other, and the interaction between the components ensures the strength of the concrete.

[0095] 7. During the mixing process of the concrete of the present invention, half of the fiber and fine aggregate are added and mixed at the same time, and the rest is generally added and mixed for 30 seconds to 1 minute after all materials are mixed, so as to ensure the uniform distribution of the fiber in the concrete. This helps to give full play to the reinforcing effect of the steel fiber;

[0096] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. A high-strength and high-performance radiation-proof concrete, characterized in that: The concrete comprises water, cementitious material, fine aggregate, special-shaped steel shot, water reducing agent and fiber; the cementitious material comprises cement and mineral admixture, the mineral admixture comprises fly ash and barite powder in a weight ratio of 1:1-2, and the fiber is copper-plated microfilament steel fiber coated with epoxy resin on the surface; the concrete comprises, by weight: 140-180 parts of water, 200-400 parts of cement, 100-200 parts of mineral admixture, 1200-1500 parts of lead-zinc ore sand with a particle size of 0.1-0.6mm, 600-1000 parts of lead-zinc ore sand with a particle size of 0.6-1.18mm, 100-500 parts of special-shaped steel shot with a particle size of 0.1-2mm, 10-20 parts of polycarboxylic acid high-efficiency water reducing agent, and 30-50 parts of fiber.

2. The high-strength and high-performance radiation-proof concrete according to claim 1, characterized in that: The concrete includes the following raw material components in parts by weight: 250 parts of cement, 150 parts of mineral admixture, 1383 parts of lead-zinc ore sand with a particle size of 0.1-0.6 mm, 847 parts of lead-zinc ore sand with a particle size of 0.6-1.18 mm, 18 parts of polycarboxylic acid high-efficiency water reducing agent, 39 parts of fiber, 160 parts of water; 147 parts of special-shaped steel shot with a particle size of 0.1-2 mm, and the mineral admixture is composed of fly ash and barite powder in a weight ratio of 1:

1.

3. The high-strength and high-performance radiation-proof concrete according to claim 1, characterized in that: The lead-zinc ore sand contains 2%-5% lead, 8%-15% zinc, 20%-30% sulfur and 50%-65% oxides, wherein the oxides include one or more of silicon, sulfur, iron and cadmium oxides, and the specific gravity of the lead-zinc ore sand is 4.5g / cm 3 .

4. The high-strength and high-performance radiation-proof concrete according to claim 1, characterized in that: The particle size of the special-shaped steel shot is 0.1-2mm, and the specific gravity of the special-shaped steel shot is 7.8g / cm 3 The surface of the special-shaped steel shot has a circle of concave holes.

5. The high-strength and high-performance radiation-proof concrete according to claim 1, characterized in that: The fly ash has a particle size of 0.5-100 μm, a water content of 1-5%, a sulfur trioxide content of 0.5-1%, and a loss on ignition of 1.5-3%; The barite powder has a particle size of 0.1-1 μm and a bulk density of 3200 kg / m 3 , moisture content is less than 5%.

6. The high-strength and high-performance radiation-proof concrete according to claim 1, characterized in that: The copper-plated microfilament steel fiber comprises a layer of copper plated on the surface of the steel fiber.

7. The high-strength and high-performance radiation-proof concrete according to claim 1, characterized in that: The polycarboxylic acid high-efficiency water-reducing agent has a water-reducing rate of 18%, and a 1h slump retention rate of not less than 95%.

8. The high-strength and high-performance radiation-proof concrete according to claim 1, characterized in that: The barite powder is pretreated as follows: the barite powder is calcined in a stepped manner including at least four calcination stages, the calcination temperature of the first stage is 105-110°C, the calcination temperature of the second stage is 450-500°C, the calcination temperature of the third stage is 850-900°C, and the calcination temperature of the fourth stage is 1000°C-1300°C, wherein the insulation time of the first three stages is 30-120min, the insulation time of the fourth stage is 1h-3h, and the heating rate of each stage is 2-10°C / min.

9. A method for preparing high-strength and high-performance radiation-proof concrete according to any one of claims 1 to 9, characterized in that: The specific steps include: Cement, mineral admixture, half of the fiber, fine aggregates, which are lead-zinc ore sand with a particle size of 0.1-0.6 mm, lead-zinc ore sand with a particle size of 0.6-1.18 mm, and special-shaped steel shots are added into a mixer, and after the first stirring and mixing, the other half of the fiber is added and stirred for a second time to obtain a mixture, and then 140-180 parts of water and 10-20 parts of polycarboxylate high-efficiency water reducing agent are added to the mixture to make it enter a fully mixed state, and stirred for a third time until it is uniform to obtain the high-strength and high-performance radiation-proof concrete.

10. The method according to claim 9, characterized in that The first stirring time is 2-3 min, the second stirring time is 0.5-1 min, the third stirring time is 5-10 min, and the stirring speed is 60 rpm.